Scholia vetera in Sophoclis Trachinias - Xenis, Georgios A. (Sammlung griechischer und lateinischer Grammatiker ;, 2010)
Scholars have been seeking to understand Sophocles' Trachiniae for over two millennia. The beginnings of this long tradition of the play's interpretation are in Hellenistic Alexandria and are now being represented by a series of notes which have survived in the margins of medieval manuscripts. The book offers an English introduction and an authoritative new critical text of these notes based on a thorough review of the manuscript evidence and the best modern scholarship. The critical text is accompanied by a apparatus criticus, and is placed in its scholarly context by means of a rich collectio.